PENGARUH METODE BRAIN GYM DALAM MENINGKATKAN KEMAMPUAN MENGINGAT ANAK USIA 5-6 TAHUN - Syiva Nurul Ain; Arifah A Riyanto; Ririn Hunafa Lestari (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Early Childhood according to experts mention the golden age period, a time when the period is sensitive to good stimuli for its development. Any stimulation given to children and accepted by children will give birth to a new connection. The strength of a child's automatic brain cell network will spur aspects of a child's development to be more developed such as cognitive, social-emotional, creativity, language, and so on. Therefore, many programs are currently being developed which aim to stimulate an increase in cognitive function, one of which is Brain Gym. To find out the effect of the brain gym on an exercise program that focuses on specific physical activities to activate brain function, thereby increasing cognitive performance and making it easier to receive learning. This research is an experimental research with quassy experiment research design (quasi-experiment) with respondents as many as 32 respondents divided into two groups, namely, the experimental group (n = 16) and the control group (n = 16). The results showed that children in the brain gym experimental group had a higher posttest score of 44 than 32 points from the pretest value while the control group actually experienced a slight decline in the average value of 33 points lower in the posttest value of the experimental group. The results of the pretest t-test are 0.074, so the value is more than 0.05, meaning there is an increase in ability to remember. While it is seen that the significance value is 0.000, the significance is <0.05 so that H0 is rejected, which means there is a difference between the experimental class and the control class . Brain gym has an influence on cognitive function in children significantly compared to the control group without treatment brain gym.Setiap rangsangan yang diberikan kepada anak akan diterima oleh anak untuk menghasilkan jaringan otak yang baru. Kuatnya jaringan sel otak anak, otomatis akan memacu aspek-aspek perkembangan anak menjadi semakin berkembang seperti kognitif salah satunya kemampuan daya ingat. Salah satu  kegiatan yang bertujuan untuk mengembangkan fungsi kognitif adalah Brain Gym. Berdasarkan pernyataan tersebut, tujuan dari penelitian ini Untuk mengetahui pengaruh brain gym terhadap kemampuan mengingat anak usia 4-5 tahun. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian quassy experiment dengan responden sebanyak 32 responden yang dibagi kedalam dua kelompok yaitu, kelompok eksperimen (n=16) dan kelompok kontrol (n=16). Hasil uji t-tes pre test adalah 0,074 dengan demikian nilai tersebut lebih dari 0,05 artinya ada peningkatan kemampuan mengingat yang dilihat dari nilai signifikansi 0.000 < 0,05 sehingga H0 ditolak yang berarti terdapat perbedaan kemampuan akhir antara kelas eksperimen dan kelas kontrol. Maka dari itu metode brain gym memiliki pengaruh terhadap kemampuan menginat pada anak dibandingkan dengan kelompok kontrol tanpa treatment brain gym, sehingga metode brain gyam dapat dijadikan alternatif metode pembelajaran dalam mengembangkan kemampuan mengingat anak usia 4-5 tahun.